2018
DOI: 10.15421/2018_183
|View full text |Cite
|
Sign up to set email alerts
|

A review of lignocellulosic biochar modification towards enhanced biochar selectivity and adsorption capacity of potentially toxic elements

Abstract: Biochar, which is rich in aromatic carbon and minerals, is a product of biomass pyrolysis at temperatures ranging from 350°C to 1000°C in oxygen-limited environments. In recent years biochar has generated much interest in the field of water treatment in view of low production costs, availability of the feedstock (e.g. lignocellulosic biomass waste) and adsorptive properties. This review incorporates researches on artificial and natural modifications of biochar towards adsorption of potentially toxic elements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The author attributed the significant modification in morphological and physical-chemical properties to the synergetic effect of the CEM method. Despite above CuCl 2 and MgCl 2 , various metallic salts, such as AlCl 3 , CaCl 2 , MnCl 2 and ZnCl 2 , have also been widely used to pretreat biomass in the production of biochar-based metallic oxides/ hydroxide composites (Wang et al 2018b;Fang et al 2015;Wang et al 2015c;Chemerys et al 2018;Li et al 2018e). The resulting composites usually exhibit dramatic changes in morphological and physical-chemical properties, leading to better performance in environmental treatment.…”
Section: Nanometallic Oxides/hydroxide Biochar Compositesmentioning
confidence: 99%
“…The author attributed the significant modification in morphological and physical-chemical properties to the synergetic effect of the CEM method. Despite above CuCl 2 and MgCl 2 , various metallic salts, such as AlCl 3 , CaCl 2 , MnCl 2 and ZnCl 2 , have also been widely used to pretreat biomass in the production of biochar-based metallic oxides/ hydroxide composites (Wang et al 2018b;Fang et al 2015;Wang et al 2015c;Chemerys et al 2018;Li et al 2018e). The resulting composites usually exhibit dramatic changes in morphological and physical-chemical properties, leading to better performance in environmental treatment.…”
Section: Nanometallic Oxides/hydroxide Biochar Compositesmentioning
confidence: 99%
“…Thus, it can be observed that mustard waste biomass and soy waste biomass required a high pyrolysis temperature (650 • C) compared with algae waste biomass (600 • C). This can be explained if the biomass of algae waste is considered to have a low content of cellulose and hemicellulose [34], and therefore the temperature required to carbonize the protein molecules in its structure is lower. However, it should be noted that in the mentioned pyrolysis conditions, the mass decrease is higher than 40% and the order is: Mustard waste biomass > soy waste biomass > algae waste biomass.…”
Section: Characterization Of the Biochar Samplesmentioning
confidence: 99%
“…The ash generated during pyrolysis remains trapped inside the pores of the biochar, thus lowering the surface area . The surface area trend can be further explained as based on the following explanation: lignocellulose contains hemicellulose (40–50%), cellulose (20–40%), and lignin (10–40%) . Decomposition of hemicellulose takes place mainly at 250–350 °C, followed by cellulose at 325–400 °C and lignin at 300–550 °C .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The surface area trend can be further explained as based on the following explanation: lignocellulose contains hemicellulose (40–50%), cellulose (20–40%), and lignin (10–40%) . Decomposition of hemicellulose takes place mainly at 250–350 °C, followed by cellulose at 325–400 °C and lignin at 300–550 °C . Thus, biochars composed of cellulose and hemicellulose decompose easier and possess higher surface areas .…”
Section: Results and Discussionmentioning
confidence: 99%